Pengembangan Aplikasi Layanan Kesehatan berbasis Web untuk Skrining Pendengaran menggunakan Arsitektur Clean (Studi Kasus: Fakultas Kedokteran Universitas Brawijaya) - Harun Ulum Fajar; Agi Putra Kharisma; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The COVID-19 pandemic has had an impact on society. Interaction restrictions lead to the accessibility of public services, including public health services. Currently, the Faculty of Medicine, Universitas Brawijaya has conducted an online hearing screening process. However, it still does not meet the needs of doctors. The author initiated a research entitled